Challenges regarding the control of environmental sources of contamination in healthcare settings in low-and middle-income countries - a narrative review - Folasade T. Ogunsola; Shaheen Mehtar (Antimicrobial Resistance and Infection Control, 2020)
Abstract Background Healthcare-associated infections (HAI) especially outbreaks of multi-drug-resistant organisms within hospitals are recognized as a major contributor to morbidity and mortality of hospitalized patients. The healthcare environment can act as an amplifier of HAI during outbreaks. The risk of acquiring HAI are 20 times higher in Low-and-middle-income countries. The purpose of this article is to review the challenges associated with controlling environmental contamination in low and lower-middle income countries (LMIC), highlighting possible solutions. Method This is a narrative review. A literature search was carried out in Google scholar, PubMed, Science Direct, EBSCOHOST, CENGAGE, Scopus, ProQuest, Clinical Key and African journals online using the key words - Health care Associated Infections (HCAIs) in LMICs, Challenges of HAIs in LMIC, Challenges of Prevention and Control of HAIs in LMICs, Environment of care and infection transmission, Contaminated environment and HAIs. Results From the accessed databases, 1872 articles related to environmental sources of contamination in healthcare settings were found. Of these, only 530 articles focused on LMICs. However, only 186 articles met the inclusion criteria studies published in English, conducted between 2000 and 2019 and exploring environmental sources of contamination in LMIC healthcare settings). The sources of environmental contamination in healthcare are numerous and commonly associated with poor governance, Inadequate infrastructure, human capacity and inadequate funding. Low awareness exists at all levels as to the role of the environment in healthcare outcomes and may explain in part the low priority given for funding. Conclusion Leadership and trained personnel, both Infection prevention and control practitioners and cleaners are crucial to drive and sustain the process to reduce environmental contamination in healthcare environments.